Optimized Saccharification of Carboxymethyl Cellulose (CMC) using Free and Immobilized Cellulase from Aspergillus niger - Olajuyigbe, F. M.; Dele-Joshua, M. T.; Cornelius, O.; Fatokun, C. O.; Dada, O. E.; Adubiina, D. B. (Journal of Science, Technology and Innovation Research, 2025)
Cellulase immobilization on solid supports is a revolutionary approach towards making cellulose hydrolysis economically viable at the industrial scale. Immobilized cellulases have significant advantages in operation stability, reusability, and affinity to the substrate over free enzymes. These advantages significantly reduce the enzyme usage, product contamination and allow continuous or repeated-batch processing, which are critical to economic industrial biocatalysis. In this study, we applied sodium alginate as a solid support in the immobilization of Aspergillus Niger cellulase. The model substrate used was carboxymethyl cellulose (CMC). The influence of pH, temperature, and substrate concentration on the saccharification of CMC by free and immobilized cellulase from A. niger were determined. Re-useability of the immobilized cellulase in the saccharification of CMC was also examined. CMC hydrolysis by both free and immobilized A. niger cellulase recorded highest yield at pH 6.0 and 3.0 with 10.9% and 8.5%, respectively. Optimal temperature for CMC hydrolysis by free and immobilized A. niger cellulase was obtained at 50°C and 40°C with 9.2% and 7.20% saccharification, respectively. Optimal saccharification of CMC by free and immobilized cellulase from A. niger was obtained at 1.5% and 0.5% (w/v) substrate concentration with 23.32% and 11.39% saccharification, respectively. Overall, immobilized cellulase systems enable higher catalytic productivity, lower enzyme cost, and improved process robustness making cellulase immobilization a critical enabler in industrial-scale biomass valorization and biofuel production.